2009
DOI: 10.1007/s11096-009-9349-1
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6*4, CYP3A5*3 and ABCB1 3435T polymorphisms and drug-related falls in elderly people

Abstract: The hypothesis that 'poor metabolizers' have an increased fall risk was not confirmed. A larger study population is needed to confirm the potential association that was seen between CYP2D6*4 and ABCB1 3435T polymorphisms and drug-related falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
9
0
1
Order By: Relevance
“…A similar result was observed in the P-gp subgroup (3435TT versus 3435CC + 3435CT), with an OR of 2.1 (95% CI 0.2–17.2). For users of CYP3A5 substrates, there appeared to be no difference in fall risk between PMs (n=49) and EMs + IMs (n=14) (OR 0.9, 95% CI 0.2–3.3) 28. The lack of statistical significance of the increased OR seen in the CYP2D6 and P-gp subgroup might be due to the fact that the cohorts were insufficiently powered for the subanalysis.…”
Section: Resultsmentioning
confidence: 93%
“…A similar result was observed in the P-gp subgroup (3435TT versus 3435CC + 3435CT), with an OR of 2.1 (95% CI 0.2–17.2). For users of CYP3A5 substrates, there appeared to be no difference in fall risk between PMs (n=49) and EMs + IMs (n=14) (OR 0.9, 95% CI 0.2–3.3) 28. The lack of statistical significance of the increased OR seen in the CYP2D6 and P-gp subgroup might be due to the fact that the cohorts were insufficiently powered for the subanalysis.…”
Section: Resultsmentioning
confidence: 93%
“…Panagiotidis et al 73 also investigated that no correlation between the number of CYP2D6 alleles and side effects exists. Blonk et al 74 have also observed no significant CYP2D6*2 allele with drug-related falls in elderly people. In a recent study, Tiwari et al 75 also showed no significant association between CYP2D6*2 with tradative dyskinesia (P 5 0.935) in North Indian patients with chronic Schizophrenia.…”
Section: Discussionmentioning
confidence: 94%
“…For users of CYP3A5 substrates, there appeared to be no difference in fall risk between PMs (n=49) and EMs + IMs (n=14) (OR 0.9, 95% CI 0.2-3.3). 28 The lack of statistical significance of the increased OR seen in the CYP2D6 and P-gp subgroup might be due to the fact that the cohorts were insufficiently powered for the subanalysis. It is worth conducting a prospective study in a larger population to confirm the possible association of genetic polymorphism with fall risk in the elderly.…”
Section: Genetic Polymorphismmentioning
confidence: 99%